Functional Proton MRI in Emphysematous Rats. Issue 12 (December 2015) - Bianchi, Andrea; Tibiletti, Marta; Kjørstad, Åsmund; Birk, Gerald; Schad, Lothar R.; Stierstorfer, Birgit; Stiller, Detlef; Rasche, Volker
Abstract : Objective: To demonstrate the feasibility of proton magnetic resonance imaging (MRI) ventilation–related maps in rodents for the evaluation of lung function in the presence of pancreatic porcine elastase (PPE)-induced emphysema. Materials and Methods: Twelve rats were equally divided into 3 groups: group 1 (no administration of PPE); group 2 (PPE selectively only in the left lung); and group 3 (PPE administered in both lungs). Magnetic resonance imaging (MRI) and computed tomographic (CT) data were acquired at baseline, at 2 weeks and 4 weeks after administration, after which the animals were euthanized. The MRI protocol comprised a golden angle 2-dimensional ultrashort echo time MRI sequence [echo time, 0.343 millisecond (ms); repetition time, 120 ms; 12 slides with thickness, 1 mm; acquisition time, 30 minutes], from which inspiration and expiration images were reconstructed after the extraction of a self-gating signal. Inspiration images were registered to images at expiration, and expansion maps were created by calculating the specific difference in signal intensity. The lungs were segmented, and the mean specific expansion (MSE) calculated as an established surrogate for fractional ventilation. Computed tomographic data provided lung density (peak of the Hounsfield unit histogram, HU_P), whereas histology provided the mean linear intercept for each lung. Results: Two weeks after administration, the control group had a mean MSE in both lungs corresponding to 96% of the baseline. Group 2 had 85% of the baseline, and group 3 had 57%. Considering the PPE-treated lungs alone, a significant reduction in MSE of 27% at 2 weeks and 40% at 4 weeks was found with respect to nontreated lungs. Significant correlations between HU_P and MSE were found at all time points (baseline: r = 0.606, P = 0.0017; 2 weeks: r = 0.837, P ⩽ 0.0001; 4 weeks: r = 0.765, P < 0.0001; all time points: r = 0.739, P < 0.0001). Mean linear intercept values significantly correlated both with MRI MSE ( r = −0.770, P < 0.0001) and with CT HU_P ( r = −0.882, P < 0.0001). Discussion: The calculated ventilation-related maps showed a reduction of function in the PPE-treated lungs, both compared to the nontreated lungs and to the baseline values. Moreover, a good agreement between MRI-measured MSE, CT, and histology data quantitatively supports the presence of ventilation deficit in emphysematous lungs. In this work, we have demonstrated the feasibility of ventilation-related maps from non–contrast-enhanced 1 H lung MRI, which were capable of tracking changes in lung function over time in emphysematous rats. Abstract : Supplemental digital content is available in the text.